A reputation-based secure scheme in vehicular ad hoc networks. (2015) - Li, Xiaoqing; Liu, Jicheng; Li, Xuejun; Li, Hui
In recent years trust management has become a main method to ensure the security of vehicular ad-hoc networks (VANETs). However, most of the existing trust establishment approaches cannot handle the rapidly changing environment of VANETs appropriately. In this paper, we propose a Reputation-based Global Trust Establishment scheme (RGTE). The scheme introduces a solution to share the trust information in VANETs safely by applying statistical laws, which makes it more efficient and accurate to establish trust in rapidly changing environment. Moreover, we detect a bad node by dynamic threshold according to real-time reputation status of the network. Analysis shows that RGTE is more effective in confidence-building, security assurance and adaptability.